San Francisco's International Hotel : mobilizing the Filipino American community in the anti-eviction movement - Habal, Estella, 1949- (Temple University Press, 2007)
How a protest galvanized a cultural identity for Filipino Americans.
Keywords: Older people -- Housing -- California -- San Francisco.; Eviction -- California -- San Francisco.; Filipino Americans -- California -- San Francisco.; Expulsion (Droit) -- Californie -- San Francisco.; Américains d'origine philippine -- Californie -- San Francisco.; FAMILY & RELATIONSHIPS -- Abuse -- Elder Abuse.; FAMILY & RELATIONSHIPS -- Eldercare.; SOCIAL SCIENCE -- General.; Eviction; Filipino Americans; Older people -- Housing; California -- San Francisco